Izkrivljanje realističnega pripovednega vzorca v Kraigherjevi Kristi Albi - Gacoin-Marks, Florence (Jezik in slovstvo, 2002)
Slovene literary theory usually places Lojz Kraigher among the second generation naturalists, whose work was contemporary with the new romanticism. the second generation differs from the first one in embracing naturalism much more consistently and producing texts of higer literary value. Janko Kos regards Kraigher as the most outstanding writer among the second generation naturalists, his works containing elemetns of diverse, even opposing aesthetic orientations. The paper exposes mechanisms of a less known and little explored text by Kraigher, which perfectly mathes Kos's definition. Is seeks to verify to what extant Kraigher's 1932 Krista Alba is an original textin the context of European naturalism, whose late representative Kraigher was.
Keywords: Kraigher, Lojz, 1877-1959; Slovene literature; slovenska književnost; naturalizem; nova romantika; literarne študije; Kraigher, Lojz: Krista Alba